Pradigma dan Revolusi Ilmu Pengetahuan Perspektif Thomas Kuhn - komarudin, Komarudin (YASIN, 2021)
Science at this time has entered the realm of development of positivism. This makes it a separator between what is called scientific and what is said to be unscientific in science and makes space science in the scientific world narrow with authoritative benchmarks. Therefore, this study uses a phenomenological approach according to the philosophy of science in order to get to the core of the problem and in-depth solutions related to the discussion of science. The method used in this research is a descriptive method in which to find meanings that sometimes the problems are combined into a narrative so that they can explain the core problems. And from this research, it can be gathered that one of the figures who criticizes positism is Thomas Khun. Thomas Khun invites researchers to switch to a pradigmatic perspective with this perspective being able to expand the scope of science in every aspect of life, including in the social field.